The Correlation Among Language Barriers, Language Acquisition and Language Development in Society - Afore Tahir Harefa; Berlin Sibarani (Journal on Education, 2024)
Language acquisition is a complex process and is influenced by various factors such as environment, nutrition, and social interaction. This study aims to identify language acquisition barriers faced by sixth grade elementary school students in the community. Through qualitative research methods, observations, interviews and reading tasks were conducted with 30 children, fifteen of whom worked part-time after school, and fifteen of whom did not. Findings indicated a significant difference in language acquisition between the two groups, leading to the identification of eight factors that impede language development. These factors included lack of learning activities at home, excessive focus on work or non-academic activities, malnutrition, limited two-way interaction, lack of attention when communicating, excessive gadget use, and low self-confidence. Understanding these barriers provides insights for educators, parents and policy makers to create a supportive environment that encourages effective language development in children.